Evidence-based dentistry: an introduction - Marjolijn Hovius (Journal compilation 2007 Blackwell Munksgaard, 2007)
This book introduces the basic epidemiological and statistical aspects of research to help dental hygienists and dentists as well as students in reading and understanding scientific reports.